Effect of dietary supplementation of grape seed extract on the growth performance, lipid profile, antioxidant status and immune response of broiler chickens. (2nd November 2016) - Farahat, M. H.; Abdallah, F. M.; Ali, H. A.; Hernandez-Santana, A.
Abstract : Grape seed extracts (GSE) contain several beneficial bioactive constituents; therefore, can be utilized as a potential feed additive in broiler chickens. An experiment was conducted to investigate the effect of supplementation of broiler chicken diets with GSE as a natural antioxidant at levels of 125, 250, 500, 1000 and 2000 ppm on the growth performance, serum lipid profile, liver glutathione-reduced, thigh muscle malondialdehyde and humoral immune response against Newcastle disease virus vaccines. This experiment was performed during the life-span of chickens from 0 to 42 days of age. The results of broilers fed on diet supplemented by GSE were compared with those fed on the basal diet (control) or the basal diet supplemented by butylated hydroxytoluene as a synthetic antioxidant (BHT, 125 ppm). No significant differences were observed in the growth performance, percent livability, total lipid, high and very low-density lipoprotein cholesterols when the use of GSE or BHT were compared with the control. Total cholesterol and low-density lipoprotein cholesterol were significantly decreased after intake of GSE compared with BHT in the feed diet. The glutathione-reduced level in liver tissues was significantly increased by inclusion of GSE, but not by BHT. Inclusion of GSE or BHT decreased significantly the malondialdehyde level found in meat tissue. The antibody titer against Newcastle disease virus vaccines was significantly elevated in 28 and 35-day-old broiler chickens fed with a diet supplemented with GSE or BHT, the former providing a higher response. It can be concluded that GSE can be used as an effective natural antioxidant and immunostimulant agent in broiler chicken diets, and that 125 to 250 ppm can be considered as the optimum dosage.